Military contracting - Rosenthal, Jean W., 1945- (London : SAGE Publications Ltd, 2017)
Establishing a reliable supply chain to support the four-hundred-plus American military bases scattered throughout Afghanistan was considered by the U.S. military to be an eminently forbidding proposition. Whereas in Iraq, the U.S. Military was able to use neighboring friendly Kuwait as a staging ground for moving resources into the country, supply operations in Afghanistan admitted of no such simple solution. Mountainous rural Afghanistan had minimal road infrastructure and state police power was unreliable or non-existent. In planning its supply chain operations, the U.S. Military employed an unprecedented logistics model, outsourcing almost all trucking operations to private military contractors.
Originally published in Rosenthal, J. (2016). Military contracting. 16-012. New Haven, CT: Yale School of Management, Yale University. Retrieved from: https://vol11.cases.som.yale.edu/military-contracting.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Defense contracts -- United States; Business logistics -- United States